Fear of Missing Out (FoMO), Social Media Addiction, and Academic Stress: A Quantitative Study among High School Students in Sukoharjo Regency - Bangkit Ary Pratama (Universitas Ahmad Dahlan, 2026)
Background: The rapid development of the internet and social media has driven the emergence of the Fear of Missing Out (FoMO) phenomenon among adolescents, which can evolve into social media addiction and trigger academic stress. This study aims to examine the effect of FoMO and social media addiction on academic stress among high school students in Sukoharjo Regency. Method: This research used a quantitative analytic design with a cross-sectional approach. The sample consisted of 110 high school students aged 15–19 years in Sukoharjo Regency, selected through accidental sampling. Data were collected using validated questionnaires, including the FoMO Scale, BSMAS, and ESSA. A multiple linear regression model was applied to analyze the collected data. Results: The results showed that FoMO partially had a significant positive effect on academic stress (t = 3.611, p < 0.001). Social media addiction also partially had a significant positive effect on academic stress (t = 3.422, p = 0.001). Simultaneously, FoMO and social media addiction significantly affected academic stress (F = 22.284, p < 0.001), contributing 29% to the variance in academic stress. Conclusion: FoMO and social media addiction significantly escalate academic stress among high school students in Sukoharjo Regency, acting as both partial and simultaneous contributors.